K.H. van Dalen-Oskam, K.A.C. Depuydt, W.J.J. Pijnenburg and T.H. Schoonheim (Editors). Dictionaries of Medieval Germanic Languages - du Plessis, J.C.M.D. (Lexikos, 2001)
From 4 to 7 July 1994 the University of Leeds hosted the first International Medieval Congress. Three sessions were dedicated to "Dictionaries of Medieval Languages". They dealt with the following themes: "Projects", in which several dictionary projects were presented, "Historical Background", which focuses on the importance of extensive knowledge of the historical background when working on a dictionary of a medieval language, and "Scribes and Scholars", elaborating on the philological problems a lexicographer encounters when working with old handwritten source material and its editions.